A Review of Trends and Issue of Cybersecurity and Privacy Challenges in Digital Libraries (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The digitization of digital libraries has transformed them into an important infrastructure to access, preserve, and share knowledge; yet, their speedy transformation and reliance on networked technologies have increased the vulnerability of Cybersecurity and privacy. This paper reflects on recent developments, risks, and unsolved challenges in Cybersecurity and privacy in digital libraries. The study synthesizes evidence on the major vectors of attack, including phishing, Ransomware, insider threats, and third-party supply-chain vulnerabilities based on peer-reviewed literature, international guidelines, incident reports, and trustworthy web-based sources. Special focus is made on the privacy dilemmas of the user data collection and processing, such as search history, logs of access, and authentication credentials, which prompt privacy concerns of surveillance, profiling, and adherence to regulations. The paper also examines the systems of governance, policy measures, and technical protection taken by libraries, and identifies areas of discrepancies between suggested standards and practice. New threats of cloud systems, discovery systems powered by analytics, and artificial intelligence are discussed, too. The paper concludes by stating that even though awareness of Cybersecurity and privacy has grown, digital libraries are still unprepared, and integration of governance, privacy-by-design, and continued investment in security capabilities are needed.